P345 Temporal changes of left atrial function after orthotopic heart transplantation in a single-center prospective study. (17th January 2020) - Dohy, Z; Czimbalmos, C; Assabiny, A; Tarjanyi, Z; Szakal-Toth, Z; Parazs, N; Toth, A; Suhai, F; Kiraly, A; Edes, I; Becker, D; Sax, B; et al.
Abstract: Funding Acknowledgements: Project no. NVKP_16-1-2016-0017 has been implemented with the support provided from the National Research, Development and Innovation Fund of Hungary The geometry and function of the left atrium (LA) change after orthotopic heart transplantation (HTX) with bicaval technique, as the LA has a recipient part around the pulmonary veins and a donor part, and these often contract separately. Because of this altered LA function, the recognition of left ventricular diastolic dysfunction can be challenging. The standard echocardiographic diastolic parameters are often in abnormal range in HTX patients despite of normal left ventricular diastolic function. The aim of our prospective study was to investigate the LA volumes and function and their temporal changes after HTX using cardiac magnetic resonance (CMR). To better understand the cardiac characteristics of HTX patients, we started a prospective trial in January 2018. CMR was performed at one, three and six months after HTX. Left atrial contour detection was performed in 2- and 4-chamber views. Patients who had ≥Grade II allograft rejection before the CMR examination, were excluded (n = 2). In the remaining HTX patients (n = 21) and in a control group (n = 21) LA ejection fraction (EF), BSA-corrected maximum and minimum LA volume (Vi), stroke volume (SVi) were evaluated using bi-plane mode. LA global longitudinal strain (GLS) was defined with CMR based deformation imaging, called feature tracking. HTX patients had significantly higher LA volumes (maxLAVi 71 ± 22 vs. 47 ± 6 ml/m2, minLAVi 53 ± 22 vs. 18 ± 5 ml/m2) lower LASVi (19 ± 7 vs. 29 ± 4 ml/m2), LAEF (27 ± 10 vs. 62 ± 8%) and LA-GLS (8 ± 3 vs. 39 ± 10%) compared to the control group (p < 0.0001). Analysing the temporal changes in HTX patients, we found an increase in the LAEF (26 ± 8 vs. 30 ± 5%) and LA-GLS (8 ± 3 vs. 11 ± 3%) at three months (p < 0.05), there was no significant difference between the LA parameters at three and six months. Better understanding of the changes of left atrial function after HTX could help us to recognise pathological conditions.